Efficacy and safety of esketamine for pediatric gastrointestinal endoscopy: a meta-analysis and trial sequential analysis - Yu, Yunfeng; Deng, Juan; Tong, Keke; Yin, Yuman; Yu, Rong; Tan, Chuanchuan (Frontiers in Pharmacology, 2024)
Objective: The role of esketamine in pediatric gastrointestinal endoscopy is still unclear. This study aims to evaluate the efficacy and safety of esketamine for pediatric gastrointestinal endoscopy. Methods: Clinical trials of esketamine for pediatric gastrointestinal endoscopy were searched in eight common databases, up to October 2023. These clinical trials were included in the meta-analysis and trial sequential analysis (TSA). The risk ratio (RR) and weighted mean difference (WMD) were used as the effect sizes for dichotomous variables and continuity variables, respectively. When the heterogeneity test showed I2<50%, the fixed effects model was used for the meta-analysis and TSA; Otherwise, the random effects model was used for them. Results: In terms of efficacy endpoints, the meta-analysis showed that compared with placebo or blank, esketamine significantly decreased recovery time by 2.34 min (WMD -2.34; 95%Confidence interval [CI] -3.65, -1.02; P=0.0005) and propofol consumption by 0.70 mg/kg (WMD -0.70; 95%CI -0.98, -0.43; P<0.00001) , and increased mean heart rate by 4.77 beats/min (WMD 4.77; 95%CI 2.67, 6.87; P<0.00001) and mean arterial pressure by 3.10 mmHg (WMD 3.10; 95%CI 1.52, 4.67; P=0.0001), while induction time and mean blood oxygen remained comparable. TSA indicated conclusive evidence for these benefits. In terms of safety endpoints, the meta-analysis revealed that esketamine significantly reduced involuntary movements by 59% (RR 0.41; 95%CI 0.22, 0.76; P=0.005) and choking by 51% (RR 0.49; 95%CI 0.26, 0.92; P=0.03), while significantly increasing dizziness by 98% (RR 1.98; 95%CI 1.11, 3.56; P=0.02) and there were no significant differences in total adverse events, respiratory depression, and vomiting. TSA demonstrated conclusive evidence for involuntary movements and dizziness. Low-dose analysis showed that esketamine at ≤0.3 mg/kg significantly reduced recovery time, propofol consumption and involuntary movements, and significantly increasing mean heart rate, with no increase in dizziness. The Begg's test (P=0.327) and the Egger's test (P=0.413) indicated no significant publication bias, yet the funnel plot suggested potential publication bias. Conclusion: Esketamine is an effective adjuvant anesthesia for children undergoing gastrointestinal endoscopy. However, the general dose of esketamine may increase the risk of dizziness, which can be avoided by administering a low dose (≤0.3 mg/kg).